Photocycloreversions within single polymer chains. Issue 41 (30th September 2020) - Liu, Modan; Wenzel, Wolfgang; Frisch, Hendrik
Abstract : Reversible photocycloadditions hold great potential to control formation and fissure of bonds. However, the wavelength selective addressability of cycloaddition and -reversion was found to be lost in the confined environment of single polymer chains. Abstract : Reversible photocycloadditions hold great potential for the development of remote-controlled chemical networks: the bond forming cycloaddition can be initiated with one wavelength, while the formed cycloadduct can be reversed upon irradiation with a shorter wavelength. Herein, we investigate photocycloreversions within the confined environment of single polymer chains and reveal that the orthogonal addressability of cycloaddition and cycloreversion is drastically limited within the polymer coil: both, shorter and longer wavelengths ( λ = 330 and 430 nm) induce effective intra–macromolecular crosslinking of single polymer chains into single chain nanoparticles (SCNPs). To elucidate the experimentally observed behaviour, we developed a comprehensive model based on coarse-grained molecular dynamics (MD) simulations, which allows simulation of the number of crosslinking points along with the morphology of the polymer coil under different irradiation wavelengths. The combination of experimental results and simulation revealed that irradiation at a shorter wavelength ( λ = 330 nm) gives rise to a photostationary state where photocyclo-addition and -reversion are occurring concomitantly. Under these conditions, covalent bonds are constantly formed and broken, allowing a dynamic rearrangement of the intra-macromolecular crosslinks of the SCNP, yet no decrosslinking into the linear precursor polymer. The developed SCNP system may serve as a blueprint for understanding the effect the confined environment has on photostationary states within polymer networks.